Contests, NGOs and decentralizing aid - Gil S. Epstein; Ira N. Gang (Institute for the Study of Labor (IZA), 2005)
International donors usually have particular goals they want to achieve with their foreign aid, for example, poverty alleviation. In the international aid story lobbying by potential recipient groups attempting to capture the donor's support play a potentially important role for nongovernmental organizations. We model this situation as a hierarchical contest and compare the implications of a centralized allocation process with a decentralized allocation process with nongovernmental organizations as intermediaries.
Keywords: F35; D72; 330; contests; NGOs; aid; Entwicklungshilfe; Nichtregierungsorganisation; Allokation; Theorie